Morfogênese e interceptação luminosa em capim-Tanzânia consorciado com Estilosantes Campo Grande ou adubado com nitrogênio sob pastejo - Lins, Túlio Otávio Jardim D´Almeida (2011)
The experiment was conducted to evaluate the morphogenetics characteristics, foliar area index and light interception of pasture Tanzania grass (Panicum maximum cv. Tanzania-1) intercropping with Stylosanthes Campo Grande or fertilised with nitrogen in seasons spring and summer. The pasture was managed under continuous stocking with variable stocking rate, keeping the height between 40 and 45 cm. The experimental design was randomized complete blocks, with plots subdivided and three repetitions. The treatments evaluated were: Tanzania grass + Stylosanthes; Tanzania grass + 75 kg.ha.year-1 of N; Tanzania grass + 150 kg.ha.year-1 of N; Tanzania grass + 225 kg.ha.year-1 of N and the subplots were spring and summer seasons. We used urea and ammonia nitrate as a source of nitrogen. For the morphogenetic evaluations were marked 15 tillers per paddock and evaluated twice a week for a period of 28 days per assessment cycle. The evaluation cycles represent the spring and summer seasons. The highest values of LER were obtained in spring in the pasture that received nitrogen fertilizer. The morphogenetic features except the LER, were not affected by nitrogen fertilization or by the intercrop. There was no difference between stations evaluated for IAF and IL, however there was influence of nitrogen fertilization on those two characteristics. The highest values for LAI and LI were obtained with larger doses of nitrogen (150 and 225 kg.ha.year-1). The pasture in intercrop presented LAI and LI similar to pasture which received 75 kg.ha.year-1 of N.